Principal Supervision and its Impact on Educational Administration Services at MAN 1 Kepahiang: A Descriptive Qualitative Analysis - Susanti, Fitri; Harahap, Emmi Kholilah; Warlizasusi, Jumira (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2024)
This study explores the role of principal supervision in enhancing the quality of educational administration services at MAN 1 Kepahiang, using a descriptive qualitative methodology. The research aims to provide insights into the supervisory practices of the principal and their impact on administrative functions. Data were collected through observations, interviews, and document reviews, involving the principal, vice-principals, and administrative staff. The analysis follows Miles and Huberman's interactive model, comprising data collection, reduction, visualization, and conclusion drawing. Results indicate that effective principal supervision, characterized by a collaborative and democratic approach, significantly improves the quality of educational administration. The principal’s dual role as a manager and supervisor enhances teacher and staff performance through continuous training and problem-solving strategies. Implications of these findings suggest the need for principals to adopt proactive supervisory roles to foster a culture of continuous improvement. The study’s limitations include its focus on a single institution and the subjective nature of qualitative methods. Future research should consider broader scopes and mixed-method approaches to generalize findings and further examine effective supervisory strategies.